Metaphor in Sĕrat cariyos ringgit purwa lampahan Dora Wĕca mawi sĕkar macapat by Raden Mas Panji Arja Suparta - Muslifah, Siti (UI Scholars Hub, 2021)
The Sĕrat cariyos ringgit purwa lampahan Dora Wĕca mawi sĕkar macapat is an example of a translation of a wayang play into poetry, a popular phenomenon in the late nineteenth century. To create aesthetic effects Raden Mas Panji Arja Suparta, the author of the text, makes ample use of metaphors. Some of these metaphors are well-known literary clichés. Others, which are woven into riddles (wangsalan), bring the real world of everyday life in Java vividly into view.